2014
DOI: 10.4081/or.2014.5138
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of continuous femoral nerve block, caudal epidural block, and intravenous patient-controlled analgesia in pain control after total hip arthroplasty: a prospective randomized study

Abstract: Thirty-six patients who underwent primary unilateral total hip arthroplasty (THA) were randomly allocated to 4 groups with different pain control protocols; continuous femoral nerve block (FNB group), single-shot caudal epidural block with morphine (EB group), intravenous patient-controlled analgesia with fentanyl (IV-PCA group), and systemic administration of nonsteroidal anti-inflammatory drugs (NSAIDs group). Postoperative pain was assessed using the numerical rating scale (NRS) scores and the analgesic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Various modes of peripheral nerve blockade have been proposed and examined in previous literatures. 1 - 3 , 10 , 11 , 17 - 20 , 22 - 25 The effectiveness and safety have been examined for each of those techniques. 2 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various modes of peripheral nerve blockade have been proposed and examined in previous literatures. 1 - 3 , 10 , 11 , 17 - 20 , 22 - 25 The effectiveness and safety have been examined for each of those techniques. 2 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“… 3 , 16-20 We have described our clinical experiences, showing that continuous femoral nerve block could provide a satisfactory analgesic effect after THA procedure. 17 In this study, we compared the effectiveness and safety of continuous femoral nerve block with and without sciatic nerve blockade on pain control after THA.…”
Section: Introductionmentioning
confidence: 99%
“…The Student's t-test for continuous variables and the chisquare or Fisher's exact test for categorical variables were used to compare the baseline of the two groups. The ICDSC scores (0, 12, 24, and 36 hours after extubation), as well as the NRS scores (0, 8, 16, and 24 hours after extubation) across time points, were compared between the two groups using a repeated-measures analysis of variance. p-Values <0.05 were considered statistically significant.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Pisani et al [15] reported that continuous administration of an opioid was associated with persistent delirium in older intensive care unit (ICU) patients. Nishino et al [16] similarly found that the use of opioids should not be advocated because of the risk of analgesia-related complications, although continuous administration of opioids allows for more prolonged post-surgical analgesic effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are little data on efficacy and adverse effects of pain therapy after converting an established protocol (EA) to a modified protocol (FNB) [4,5].…”
Section: Introductionmentioning
confidence: 99%